2020
DOI: 10.37940/ajvs.2020.13.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Role of Alpha Lipoic Acid in Ameliorating the Histological Alterations of Pituitary-Testicular Axis –induced by Hydrogen Peroxide in Rats

Abstract: The present study was aimed to investigate the role of alpha-lipoic acid ( ALA) as an antioxidant against in ameliorating histological disorders of pituitary- testicular axis- induced by hydrogen peroxide (H2O2) in adult Wistar rats. Forty adult male rats were randomly divided into four equal groups (10 rats /group) and were handled daily as follows for 56 days: Control group ( C) were intubated distilled water and received ordinary tap water; group T1 were intubated 60mg/kg B.W of ALA and received ordinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
1
0
0
Order By: Relevance
“…A decrease in diameter of seminiferous tubules, high of epithelial cells, as well as number of Leydig cells in group G1 might be resulted from testicular damage induced by ROS, which enhances disrupts of structural and functional integrity. These results are consistent with the previous findings (30,32,33). It has been shown that the balance of oxidant/antioxidant status in testis is necessary for male fertility, and hence testicular oxidative stress causes adverse effects on male reproductive performance (33,34).…”
Section: Discussionsupporting
confidence: 93%
“…A decrease in diameter of seminiferous tubules, high of epithelial cells, as well as number of Leydig cells in group G1 might be resulted from testicular damage induced by ROS, which enhances disrupts of structural and functional integrity. These results are consistent with the previous findings (30,32,33). It has been shown that the balance of oxidant/antioxidant status in testis is necessary for male fertility, and hence testicular oxidative stress causes adverse effects on male reproductive performance (33,34).…”
Section: Discussionsupporting
confidence: 93%